2017
DOI: 10.3892/ijmm.2017.2972
|View full text |Cite
|
Sign up to set email alerts
|

Identification of six polymorphisms as novel susceptibility loci for ischemic or hemorrhagic stroke by exome-wide association studies

Abstract: In this study, we performed exome-wide association studies (EWASs) to identify genetic variants that confer susceptibility to ischemic stroke, intracerebral hemorrhage (ICH), or subarachnoid hemorrhage (SAH). EWAS for ischemic stroke was performed using 1,575 patients with this condition and 9,210 controls, and EWASs for ICH and SAH were performed using 673 patients with ICH, 265 patients with SAH and 9,158 controls. Analyses were performed with Illumina HumanExome-12 DNA Analysis BeadChip or Infinium Exome-24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 76 publications
0
26
0
1
Order By: Relevance
“…In our previous study ( 47 ), the median age of subjects with ischemic stroke, ICH, or SAH was 74, 71, or 60 years, respectively. We thus defined patients aged ≤65 years as early-onset cases in the present study.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…In our previous study ( 47 ), the median age of subjects with ischemic stroke, ICH, or SAH was 74, 71, or 60 years, respectively. We thus defined patients aged ≤65 years as early-onset cases in the present study.…”
Section: Methodsmentioning
confidence: 94%
“…We previously showed that four, six, or three SNPs were associated with ischemic stroke (P<0.01), ICH (P<0.05), or SAH (P<0.05), respectively, as determined by multivariable logistic regression analysis with adjustment for covariates after the initial EWAS screening among both early- and late-onset subjects with these conditions ( 47 ). The relationship of four SNPs to ischemic stroke was not replicated (P<0.05) in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…27 One of these variants (rs4520) involves a silent T-C substitution and was suggested to confer increased risk for ischemic stroke in the Chinese Han population; the other, a 3 0 UTR (rs5128) polymorphism, was actually identified as a protective factor for ischemic stroke in this population. 27 In an exome-wide association study of a Japanese cohort, Yamada et al 28 identified three different coding variants associated with ischemic stroke: two protecting alleles involving TMPRSS7 and PDIA5 and a predisposing allele in CYP4F12. TMPRSS7 encodes a serine protease involved in degradation of the extracellular membrane.…”
Section: Ischemic Cerebrovascular Diseasementioning
confidence: 99%
“…28 The 391T > M polymorphism (rs2292661) was labeled an additional protective factor. 28 CYP4F12 encodes a P450 enzyme thought to be an endoplasmic reticulum protein involved in the metabolism of inflammatory mediators. 28 The 402C > R polymorphism (rs191885206) was correlated with increased risk of ischemic stroke.…”
Section: Ischemic Cerebrovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation